Storming heaven : class composition and struggle in Italian autonomist marxism - Wright, Steve, 1958- (Pluto Press, 2002)
Storming Heaven is the first comprehensive survey of Italian autonomist theory, from its origins in the anti-stalinist and workerist left of the 1950s to its heyday twenty years later. Autonomist marxism was a political tendency which privileged themes--self-organisation, construction of identity, grassroots politics, subjects in struggle--which in many ways can be seen as the precursor of today's debates around direct action protest. Emphasising the dynamic nature of class struggle as the distinguishing feature of autonomist thought, Wright explores how its understanding of class politics developed alongside emerging social movements. Offering a critical and historical exploration of the tendency's emergence in postwar Italy, Storming Heaven moves beyond the crisis of traditional analytical frameworks on the left, and assesses the strengths and limitations of autonomist marxism as first developed by Antonio Negri, Mario Tronti, Sergio Bologna and others.